The archaeological evidence of Noah's flood [covering the Hong Kong explorers' recent discovery on Mount Ararat] - Williams, Philip Ernest (Charlotte, N.C. : Christian Leaders & Scholars Press, 2012)
This book chronicles the author?s 20-year search of the archaeological remains from ancient times to determine whether Noah?s Flood was historical and, if so, why archaeologists have not seen it. He documents what he sees as advanced but violent civilizations that were brought to a sudden end by the third-millennium BC worldwide Flood. He finds evidence on all six inhabited continents of what his forensic analysis reveals as the remains of those drowned inside their homes and cities. These elaborate burials beneath archaeological tels, mounds, and megalithic structures such as Stonehenge, even the ancient graves by the Egyptian Pyramids, have long been interpreted as inspired by religion. The author claims that is impossible due to the lack of remains from settlements and cities of the living. He traces a new worldwide dispersion of man from the Middle Bronze Age that originates in the mountains of ancient Ararat around the biblical date of Noah?s Flood. The book?s Epilogue covers the recent discovery on Mount Ararat of what appears the remains of Noah?s Ark. Williams explains the Flood as hidden by the distorted framework from which prehistory has long been studied. The book surveys evidence supporting the event and discusses the traditional difficulties presented by Noah?s Flood and Ark: the spread of human languages; dramatic faunal and climate changes from the time of the Flood; and the source and destination of water sufficient to cover the earth?s mountains. His surprising answers are powerfully supported in this well-documented book.
Pt. 1. Understanding the problem -- pt. 2. The Bible and history -- pt. 3. The roots of modern historiography -- pt. 4. Scientific prehistory and the problem of Noah's flood -- pt. 5. Finding the flood -- pt. 6. The flood's implications for science and scholarship -- pt. 7. The flood's meaning for today.
Includes bibliographical references.
Keywords: Bible -- Antiquities; Deluge; RELIGION / Antiquities & Archaeology; RELIGION / Biblical Studies / Old Testament; Electronic books